Vanadium dioxide based Fabry-Perot emitter for dynamic radiative cooling applications. (August 2017) - Taylor, Sydney; Yang, Yue; Wang, Liping
Abstract: An asymmetric Fabry-Perot emitter is proposed with a lossless dielectric spacer inserted between a vanadium dioxide (VO2 ) thin film and an opaque aluminum substrate. Switchable mid-infrared emittance has been achieved due to the insulator-to-metal transition of VO2 . When VO2 is dielectric below 341 K, the structure is highly reflective, thereby minimizing thermal radiation loss. Above 345 K, the VO2 becomes metallic and forms a Fabry-Perot resonance cavity with high broadband emissivity around 10 µm wavelength, providing a radiative cooling effect due to enhanced thermal emission. The radiative properties are calculated via a uniaxial transfer matrix method and Bruggeman effective medium theory. The physical mechanisms that provide the observed absorption enhancements are elucidated by examining the total phase shift in the multilayer structure and the phonon modes of VO2. When experiencing the VO2 phase transition, the radiative power of the proposed coating achieves a 6.5 fold enhancement for extraterrestrial spacecraft systems, and 7.3 fold enhancement for terrestrial systems such as buildings, making it a promising choice for dynamic radiative cooling applications in a variable environment. The findings here will facilitate research and development of novel coating materials for radiative cooling applications. Highlights: Dynamic radiative cooling was achieved with a VO2 -based Fabry-Perot emitter. Strong Fabry-Perot resonance was identified when VO2 is in its metallic phase. The performance was determined to be insensitive to incidence angle. The cooling power for building and spacecraft applications was investigated.